Influence of Parks and Urban Forest on the Prices of Residential Real Estate in Skopje - Pencic, D. and Trpkovska, A. (Faculty of Civil Engineering -Skopje, University Ss. Cyril and Methodius Skopje, 2017)
The focus of this research was to evaluate the influence of the Vodno urban forest and the City Park on the prices of apartments in Skopje, Republic of Macedonia. Detailed investigation and examination of the spatial relations between the residential real estates and the open green spaces (parks and urban forests) was performed utilizing the hedonic pricing method and multiple linear regressions. Quantitative research method was applied for data analyses and processing. Presented results indicate moderate negative correlation between Vodno and the apartment price in the sample, as well as weak negative correlation between the City Park and the apartment price in the sample. The Vodno urban forest and the City Park are regarded as predictors of the apartment price in the sample.
CADASTRE, GIS AND NSDI
Keywords: parks, urban forests, Vodno, City Park, hedonic pricing method, multiple linear regression.